2017
DOI: 10.1007/978-3-319-66700-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Stable Marriage with Covering Constraints–A Complete Computational Trichotomy

Abstract: We consider Stable Marriage with Covering Constraints (SMC): in this variant of Stable Marriage, we distinguish a subset of women as well as a subset of men, and we seek a matching with fewest number of blocking pairs that matches all of the distinguished people. We investigate how a set of natural parameters, namely the maximum length of preference lists for men and women, the number of distinguished men and women, and the number of blocking pairs allowed determine the computational tractability of this probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Very recently, five different works have studied hard stable matching problems from the perspective of parameterised complexity. In [29], the authors obtained results on the parameterised complexity of finding a stable matching which matches a given set of distinguished agents and has as few blocking pairs as possible. In [30] it is shown that several hard stable matching problems, including MAX SMTI, are W[1]-hard when parameterised by the treewidth of the graph obtained by adding an edge between each pair of agents that find each other mutually acceptable.…”
Section: Related Workmentioning
confidence: 99%
“…Very recently, five different works have studied hard stable matching problems from the perspective of parameterised complexity. In [29], the authors obtained results on the parameterised complexity of finding a stable matching which matches a given set of distinguished agents and has as few blocking pairs as possible. In [30] it is shown that several hard stable matching problems, including MAX SMTI, are W[1]-hard when parameterised by the treewidth of the graph obtained by adding an edge between each pair of agents that find each other mutually acceptable.…”
Section: Related Workmentioning
confidence: 99%
“…Very recently, three different works have studied hard stable matching problems from the perspective of parameterised complexity. Mnich and Schlotter [19] obtained results on the parameterised complexity of finding a stable matching which matches a given set of distinguished agents and has as few blocking pairs as possible. Gupta et al [13] showed that several hard stable matching problems, including Max SMTI, are W[1]-hard when parameterised by the treewidth of the graph obtained by adding an edge between each pair of agents that find each other mutually acceptable.…”
Section: Related Workmentioning
confidence: 99%
“…By adapting our reduction, we also answer Our results are summarized in Table 1. Besides the relevant work mentioned above there is a growing body of research regarding the parameterized complexity of preference-based stable matching problems [42,43,46,45,26,15].…”
Section: Our Contributionsmentioning
confidence: 99%